2019
DOI: 10.1126/science.aav7086
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation strengthening of aluminum alloys by room-temperature cyclic plasticity

Abstract: High-strength aluminum alloys are important for lightweighting vehicles and are extensively used in aircraft and, increasingly, in automobiles. The highest-strength aluminum alloys require a series of high-temperature “bakes” (120° to 200°C) to form a high number density of nanoparticles by solid-state precipitation. We found that a controlled, room-temperature cyclic deformation is sufficient to continuously inject vacancies into the material and to mediate the dynamic precipitation of a very fine (1- to 2-na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
104
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(109 citation statements)
references
References 18 publications
3
104
2
Order By: Relevance
“…The cell-structure could in turn create a beneficial precipitate distribution during artificial ageing, causing the precipitates to grow in a somewhat cell-like structure. The strengthening effect by cyclic plasticity was described by Sun et al [33], where cyclic deformation during natural ageing significantly enhances the strength of three aluminium alloys. They demonstrated that dislocation loops were present and atomic clusters were heterogeneously distributed throughout the material.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The cell-structure could in turn create a beneficial precipitate distribution during artificial ageing, causing the precipitates to grow in a somewhat cell-like structure. The strengthening effect by cyclic plasticity was described by Sun et al [33], where cyclic deformation during natural ageing significantly enhances the strength of three aluminium alloys. They demonstrated that dislocation loops were present and atomic clusters were heterogeneously distributed throughout the material.…”
Section: Discussionmentioning
confidence: 86%
“…It is likely that we are observing a somewhat similar effect in this study, where clustering is partly heterogeneous and dislocations become mobile during elastic straining. In the material which was subjected to cyclic deformation the precipitation free zones were absent, giving an additional positive effect on strength [33]. Strain accumulation is a steady process which tends to localise [34], and in many cases this occurs at the precipitation free zone (PFZ).…”
Section: Discussionmentioning
confidence: 99%
“…Other systems where coherent precipitates form first, whether in metallic alloys 7 or even minerals 3 are numerous and may well exhibit TDN and are worth exploring. These mechanisms are also likely to take place in real-life situations such as fatigue, creep, irradiation 40 and novel processing treatments 41 of engineering alloy components, or in the far-fromequilibrium conditions associated with 3D-printing 42 . Finally, our approach may offer a strategy for alloy design based on injection of vacancies, thus avoiding the reliance on costly or environmentally detrimental microalloying additions 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Wrought aluminum alloys, as a class of pervasive structural materials, are broadly used in aerospace and automobile sectors due to their low density, high strength to weight ratio and natural availability [1][2][3][4]. Currently, most parts made of wrought aluminum alloys are fabricated by plastic forming and precision machining [5,6].…”
Section: Introductionmentioning
confidence: 99%